Determinants of Domestic Violence during Pregnancy - Saeideh Sadeghi; MoradAli Zareipour; Nahid Ardian; Marzieh Mirshamsi; Mohammad Saeed Jadgal (Journal of Social Behavior and Community Health, 2024)
Background: Due to the importance of the issue and the fact that up-to-date studies in this topic have not been conducted in Yazd city, the present research was conducted to investigate and determine the intensity and frequency of domestic violence among pregnant women. Methods: This was a cross-sectional and descriptive study and sampling was done by simple random method. pregnant women referred to health centers in Yazd in 2021 participated in the study. For the study, 246 pregnant women were selected from 3 health centers in Yazd city in 2021. The tool used for the study was the standard questionnaire known as the Revised Conflict Tactics Scales (CTS2). This questionnaire was utilized to assess domestic violence, measures of dispute resolution, and demographic characteristics. After inputting the data into the SPSS version 26, Mann-Whitney and Kruskal-Wallis non-parametric statistical tests were used for data analysis. Results: The results showed that the average age of women was 31.47 ± 7.68 with a minimum age of 17 and a maximum of 55. The severity and frequency of the types of violence were measured, and the types of violence in the extreme state related to physical, mental, sexual, and verbal violence and resulting in physical injury were found to be 10%, 25%, 7%, 10%, and 19% respectively. Violence against pregnant mothers showed a significant relationship with the economic status of the family, the age of the mother's marriage, the education level of the parents, and the duration of their marriage (p<0.001). One of the most important variables affecting the severity and frequency of violence against pregnant women was the economic status of the family (p<0.001). Conclusion: The findings of this study show a connection between education level, economic status, and the prevalence of domestic violence. It is suggested to prioritize the development of diverse communication and problem-solving skills, as well as education related to family behavior on a wider scope.